Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

There are some questions I am curious to make sure. If you could provide references, I will appreciate it very much.

1.X and Y are two random variables. Whether is the following deductions correct or not:

(1)$X\mathop = \limits^d 0 \Rightarrow X\mathop = \limits^{a.s.} 0$ ------I think it is correct. Where to find the proof?

(2)$X-Y\mathop = \limits^d 0 \Rightarrow X\mathop = \limits^{d} Y$ ------I think it is wrong

(3)$X-Y\mathop = \limits^{a.s.} 0 \Rightarrow X\mathop = \limits^{a.s.} Y$ ------I think it is correct

2.{$X_t(w)$} is a stochastic process, how to understand the variable $\mathop {\sup }\limits_{0 \le s \le T} {X_s}(w)$? Do I understand it right? Fixed each w (the sample path), there is a sup among $\{X_s(w),s\le T\}$. So each w correspond to a value, which forms a random variable.

3.If {$X_t(w)$} is an adapted process, for $s<t$, how to understand the formula $E({X_t}|{F_s})={X_s}$, a.s.

4.what's the relation between $\mathop {\sup }\limits_{0 \le s \le T} {X_s^p}(w)$ and $[\mathop {\sup }\limits_{0 \le s \le T} {X_s}(w)]^p$, for positive p and positive process $\{X\}$.

share|cite|improve this question
these seem kind of independent, i would consider reposting as separate questions... – gt6989b Nov 1 '12 at 16:15
up vote 2 down vote accepted

1.1) I take it that $X=0$ in distribution means that $P_X=\delta_0$, where $\delta_0$ is the Dirac measure at $0$. If this is the case, then $P_X(\{0\})=\delta_0(\{0\})=1$, and hence $P(X=0)=1$. Another approach is to note that $X=0$ in distribution implies $P(|X|\leq x)=P(|0|\leq x)=1$ for every $x>0$ hence $X=0$ a.s.

1.2) If $X−Y=0$ in distribution then by 1.1 we have $X−Y=0$ a.s. and hence $X=Y$ a.s. (pure logic) and hence $X=Y$ in distribution (always true). The converse is not true. A counterexample being the following: consider $X$ uniform on $(−1,1)$ and $Y=−X$. (Thanks to did).

1.3) Yes, $X-Y=0$ a.s. means simply that $P(X-Y=0)=1$. But this is exactly the same as $P(X=Y)=1$ and hence $X=Y$ a.s.

2) If $(X_t)_{t\geq 0}$ is a stochastic process, then $\sup_{0\leq s\leq T}X_s$ is the random variable given by the pointwise identity $$ \Big(\sup_{0\leq s\leq T}X_s \Big)(\omega)=\sup_{0\leq s\leq T}X_s(\omega)=\sup \{X_s(\omega)\mid 0\leq s\leq T\}. $$ 3) The conditional expectation $E[X_t\mid\mathcal{F}_s]$ is a random variable, and hence the statement that $E[X_t\mid \mathcal{F}_s]=X_s$ means that for almost all $\omega$ we have $E[X_t\mid\mathcal{F}_s](\omega)=X_s(\omega)$. For the conditional expectation to exist you must have some kind of integrability assumption on $(X_t)_{t\geq 0}$. An integrable adapted process $(X_t)_{t\geq 0}$ that satisfies $E[X_t\mid\mathcal{F}_s]=X_s$ a.s. for all $0\leq s<t$ is called a martingale. When $\mathcal{F}_s$ is interpreted as the information available at time $s$, then the martingale property states that the best estimate of $X_t$ given the information available at time $s$ (this is $E[X_t\mid \mathcal{F}_s]$) is the variable $X_s$ itself.

4) The two would be the same since $x\mapsto x^p$ is continuous and non-decreasing for $p>0$. In general, if $f\! : \mathbb{R}\to\mathbb{R}$ is a continuous and non-decreasing function and $(x_s)_{0\leq s\leq T}\subseteq \mathbb{R}$, then $$ \sup_{0\leq s\leq T}f(x_s)\leq f\left(\sup_{0\leq s\leq T} x_s\right) $$ because $f$ is non-decreasing. Now we use the following property of the supremum: There exists $(s_n)_{n\in\mathbb{N}}\subseteq [0,T]$ such that $$ \sup_{0\leq s\leq T}x_s =\lim_{n\to\infty} x_{s_n}. $$ By continuity we have that $$ f\left(\sup_{0\leq s\leq T} x_s\right)=f\left(\lim_{n\to\infty} x_{s_n}\right)=\lim_{n\to\infty} f(x_{s_n})\leq \sup_{0\leq s\leq T}f(x_s), $$ and hence $$ f\left(\sup_{0\leq s\leq T} x_s\right)=\sup_{0\leq s\leq T}f(x_s). $$

share|cite|improve this answer
1.(2) obviously holds: if $X-Y=0$ (d) then by 1.(1) $X-Y=0$ a.s. hence $X=Y$ a.s. (pure logic) hence $X=Y$ (d) (always true). – Did Nov 1 '12 at 17:52
@jerry: See the edit. 2) Yes you understood it correctly. 4) It holds for every continuous and non-decreasing function. Not sure if this can be relaxed to any continuous function though. For the converse statement i'm not sure. – Stefan Hansen Nov 2 '12 at 10:26
For 1.(1), note that $X=0$ (d) implies that $P(|X|\leqslant x)=P(|0|\leqslant x)=1$ for every $x\gt0$ hence $X=0$ a.s. – Did Nov 2 '12 at 10:32
For 1.(2), $X=Y$ (d) cannot imply $X-Y=0$ (d): consider $X$ uniform on $(-1,1)$ and $Y=-X$. – Did Nov 2 '12 at 10:32
@Stefan@did: Thank for your help. My question is solved, during which I have learned much. I enjoy, I enjoy you kindly guys! – jerry Nov 2 '12 at 11:02

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.